2017
DOI: 10.1016/j.cllc.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Profiling of Advanced Non–Small Cell Lung Cancer in Community Settings: Gaps and Opportunities

Abstract: Genomic testing presents multiple logistical challenges for the community-based oncologist, including coordination of sample handling, long turnaround times, test reimbursement, access to targeted therapies, insufficient tissue, and patient harm from the repeat biopsies necessary if the tissue sample is insufficient. Opportunities exist for improvement in guideline adherence, possibly through new technologies such as "liquid biopsies," which obviates the need tissue biopsy samples in select settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
157
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 182 publications
(160 citation statements)
references
References 52 publications
2
157
0
1
Order By: Relevance
“…Undergenotyping, incomplete testing for all guidelinerecommended biomarkers, continues to challenge the treatment of patients with mNSCLC. In a study of patients with newly diagnosed mNSCLC recruited from 15 community clinics, only 8% of 814 patients had complete tissue genotyping for all guideline-recommended biomarkers, with almost onethird not tested for EGFR mutations or ALK fusions, 75% untested for ROS1 fusions, and more than 80% untested for the BRAF V600E mutation, MET amplifications or exon 14 skipping alterations, RET fusions, or ERBB2 mutations (8). In a larger study conducted in 166 clinics, 25% of the almost 7,000 patients were not tested for EGFR mutations or ALK fusions (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Undergenotyping, incomplete testing for all guidelinerecommended biomarkers, continues to challenge the treatment of patients with mNSCLC. In a study of patients with newly diagnosed mNSCLC recruited from 15 community clinics, only 8% of 814 patients had complete tissue genotyping for all guideline-recommended biomarkers, with almost onethird not tested for EGFR mutations or ALK fusions, 75% untested for ROS1 fusions, and more than 80% untested for the BRAF V600E mutation, MET amplifications or exon 14 skipping alterations, RET fusions, or ERBB2 mutations (8). In a larger study conducted in 166 clinics, 25% of the almost 7,000 patients were not tested for EGFR mutations or ALK fusions (9).…”
Section: Discussionmentioning
confidence: 99%
“…The increasing number of therapeutic biomarkers to be assessed in patients with newly diagnosed mNSCLC adds time to the clinical evaluation and places strain on tumor tissue availability, especially when biomarkers are assessed in a sequential manner adding additional expense (7). Real-world studies of clinical practice have demonstrated that significant numbers of patients with mNSCLC are not tested for the four guideline-recommended biomarkers with FDA-approved targeted therapies, EGFR exon 19 deletions and L858R mutation, BRAF V600E mutation, ALK fusions, and ROS1 fusions, and the majority are not tested for all eight guideline-recommended biomarkers (8,9). Utilizing comprehensive tissue next-generation sequencing (NGS) has shown promise in the ability to fully assess patients for the recommended biomarkers but remains challenged by tissue availability and the time required for guideline-complete testing.…”
Section: Introductionmentioning
confidence: 99%
“…The targeted therapy outcomes reported here are consistent with and build upon more than a dozen published studies (excluding single-patient case reports) using the same cfDNA NGS test, Guardant360. 4,[13][14]17,[22][23]30,34,[37][38][39][45][46][47] Treatment outcome studies are the gold standard for validation of genomic diagnostic tests, as concordance between plasma-and tissue-based tests is challenged by tumor spatial and temporal (acquired resistance) heterogeneity or suppression of tumor DNA shedding by treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Targeted therapies matched with driver oncogenes significantly prolong the overall survival of advanced lung cancer patients in academic-as well as community-based practice settings. [1][2][3][4] Molecular testing for somatic genomic mutations in EGFR and BRAF, and rearrangements of the ALK receptor tyrosine kinase (ALK) and ROS1 genes are associated with targeted therapy response rates two-to three-fold higher than with cytotoxic chemotherapy. [5][6][7][8][9] Other lung cancer targetable genomic driver aberrations include ERBB2 (HER2), RET, MET, and NTRK.…”
Section: Introductionmentioning
confidence: 99%
“…Of those patients who did not receive testing, 13% did not have sufficient tissue for testing EGFR/ALK on initial biopsy. 10 Both in the United States and globally, patients with NSCLC face challenges to receiving biomarker testing at many time points throughout their cancer journey. In many locations global access to health care facilities that can execute biomarker testing is limited.…”
Section: Introductionmentioning
confidence: 99%